Importance of patient reported and clinical outcomes for patients with locally advanced rectal cancer and their treating physicians. Do clinicians know what patients want? - van der Valk, Maxime J.M.; van der Sande, Marit E.; Toebes, Renee E.; Breukink, Stephanie O.; Bröker, Mirelle E.E.; Doornebosch, Pascal G.; Maliko, Nansi; Neijenhuis, Peter A.; Marinelli, Andreas W.K.S.; Peters, Femke P.; Peeters, Koen C.M.J.; Beets, Geerard L.; et al. (European journal of surgical oncology, 2020)
Several factors are included in decision making for treatment of patients with locally advanced rectal cancer, including a trade-off between risks and gains of both clinical and functional outcomes. However, it is largely unknown which outcomes are most important to patients and whether this differs between patients and clinicians. Both clinicians and patients treated for locally advanced rectal cancer were invited to fill out an online questionnaire, including a choice-based conjoint experiment. Participants were presented 14 comparisons of two hypothetical case presentations, characterized by different treatments and outcomes of care (6 attributes) and were asked to select the case with the best outcome at that moment. Hierarchical Bayes Estimation was used to calculate the relative importance (RI) of each of the six attributes. In total, 94 patients and 128 clinicians completed the questionnaire. For patients, avoiding surgery with permanent stoma was most important (RI 24.4, 95%CI 21.88–26.87) and a 2-year difference in disease-free survival was least important (RI 5.6, 95%CI 4.9–6.2). Clinicians assigned highest importance to avoiding severe and daily worries about cancer recurrence (RI 30.7, 95%CI 29.1–32.4), while this was ranked 4th by patients (RI 17.9, 95%CI 16.5–19.4, p < 0.001). When confronted with different outcomes within one case description, patients find the duration of disease free survival the least important. In addition, considerable differences were found between the importance assigned by patients and clinicians to clinical and functional outcomes, most notably in avoiding surgery with permanent stoma and worries about recurrence.